EFEKTIVITAS CENDAWAN ENTOMOPATOGEN BEAUVARIA BASSIANA TERHADAP HAMA PENGGEREK BUAH KAKAO CONOPOMORPHA CRAMERELLA SNELLLEN - Puu, Yustina Maria Silvia Wonga (AGRICA, 2010)
Cocoa pod borer Conomorpha cramerella snellen (lepidoptera: gracillaridae) is one type of the key pest which is highly responsible for drilling cocoa, which then causes the production and quality of cacao to decrease. The use of entomopathogenic fungus is one of the alternatives to cope with it. By invecting and developing within the insect, such a fungus can cause the insect to suffer from diseases which will then be responsible for their death. Beauveria bassiana are types of the entomopathogenic fungus which are used for controlling cocoa pod corer, as they are able to infect the pest trough the enzyme or toxin produced, which then leads to its death. This study aims at an effectiveness test of entomopathogenic fungus Beauveria bassiana against cocoa pod borer. This research was conducted at the Laboratory Udaya University in Bali from May to November 2010. The experimental design employed was randomized complete block design (RCBD) wich was made up of four treatments such as B0 (Control), B1 (B. bassiana in which the spore density was 105 spora/ml/); B2 (B, bassiana in which the spore density 106 spora/ml); B3 (B. bassiana in which the spore density was 107 spora/ml).  The result shows that the Larvae CPB which was infected by B. bassiana shows different treatments and responses than control. The fastest death of the larvae CPB took place on the treatments and responses than control. The fastest death of the larvae CPB took place on the treatment of B. bassiana in which spore density 107. The fastest appearance of spore took place on the treatment five days after inoculation. The fungus of B. bassiana at the spore speed of 105 and 107 caused all the larvae CPB 100% to die at five days inoculation.